Endothelial Nitric Oxide Synthase Mediates the Cerebrovascular Effects of Erythropoietin in Traumatic Brain Injury - Cruz Navarro, Jovany; Pillai, Shibu; Ponce, Lucido L.; Van, Mai; Goodman, Jerry Clay; Robertson, Claudia S. (Frontiers in Immunology, 2014)
Background: Erythropoietin (Epo) improves post-traumatic cerebral blood flow (CBF), pressure auto-regulation, and vascular reactivity to L-arginine. This study examines the dependence of these cerebral hemodynamic effects of Epo on nitric oxide (NO) generated by endothelial nitric oxide synthase (eNOS). Methods: Using laser Doppler flow imaging, CBF was monitored in wild-type (WT) and eNOS-deficient mice undergoing controlled cortical impact (CCI) followed by administration of Epo (5000 U/kg) or normal saline. Results: CBF decreased in all groups post-injury with the greatest reductions occurring at the impact site. Epo administration resulted in significantly higher CBF in the peri-contusional sites in the WT mice (70.2 ± 3.35 % in Epo-treated compared to 53 ± 3.3 % of baseline in saline-treated mice (p< .0001), but no effect was seen in the eNOS-deficient mice. No CBF differences were found at the core impact site where CBF dropped to 20-25% of baseline in all groups. Conclusion: These differences between eNOS-deficient and WT mice indicate that the EPO mediated improvement in CBF in TBI is eNOS dependent.